Estimating the value of medal success in the Olympic Games - Humphreys, B. R.; Johnson, B. K.; Mason, D. S.; Whitehead, J. C. (Journal of Sports Economics, 2018)
We estimate Canadians` willingness to pay (WTP) for medals won by Team Canada in the 2010 Winter Olympic Games using data from contingent valuation method (CVM) surveys of nationally representative samples conducted before and after the Games. The results permit an assessment of Own the Podium, a government program designed to increase Canada`s medal count. International prestige and national pride are important determinants of WTP. The results are sensitive to cost and scope, respondents` beliefs about the effectiveness of the program, as measured by expected medal count. WTP estimates suggest that Own the Podium generated benefits above its cost to a degree unique in the growing literature of sport CVM studies.